2009
DOI: 10.1152/ajplung.90538.2008
|View full text |Cite
|
Sign up to set email alerts
|

GTP cyclohydrolase I expression is regulated by nitric oxide: role of cyclic AMP

Abstract: Our previous studies have demonstrated that nitric oxide (NO) leads to nitric oxide synthase (NOS) uncoupling and an increase in NOS-derived superoxide. However, the cause of this uncoupling has not been adequately resolved. The pteridine cofactor tetrahydrobiopterin (BH(4)) is a critical determinant of endothelial NOS (eNOS) activity and coupling, and GTP cyclohydrolase I (GCH1) is the rate-limiting enzyme in its generation. Thus the initial purpose of this study was to determine whether decreases in BH(4) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 62 publications
(75 reference statements)
0
15
1
Order By: Relevance
“…The research literature has identified the cofactor tetrahydrobiopterin (BH4) as a significant player in eNOS function [187,188]. BH4 shifts the heme iron in eNOS to a high spin state, as well as increasing arginine binding, thus catalyzing the synthesis of NO by eNOS [187].…”
Section: Tetrahydrobiopterinmentioning
confidence: 99%
See 2 more Smart Citations
“…The research literature has identified the cofactor tetrahydrobiopterin (BH4) as a significant player in eNOS function [187,188]. BH4 shifts the heme iron in eNOS to a high spin state, as well as increasing arginine binding, thus catalyzing the synthesis of NO by eNOS [187].…”
Section: Tetrahydrobiopterinmentioning
confidence: 99%
“…BH4 shifts the heme iron in eNOS to a high spin state, as well as increasing arginine binding, thus catalyzing the synthesis of NO by eNOS [187]. The synthesis of BH4 from its substrate GTP is induced by IFN-γ, which, in turn, is induced by bacterial lipopolysaccharides (LPS) [189].…”
Section: Tetrahydrobiopterinmentioning
confidence: 99%
See 1 more Smart Citation
“…However, also in this case, the apparent uncoupling of eNOS does not seem to be linked to a measurable decrease in BH 4 levels. In fact, BH 4 levels and the expression of GTPCH were increased by NO donors via a mechanism linked to cyclic AMP and the cyclic AMP response element-binding protein [67]. Thus, it seems that mechanisms that regulate the BH 4 /BH 2 ratio independently of overall biopterin levels may play an important role in regulating eNOS.…”
Section: Substrate Availabilitymentioning
confidence: 99%
“…(2). GCH1 expression is also under the control of estrogens [77], possibly through a NO-mediated activation of CREB [78, 79]. Interestingly, cAMP is a strong activator of GCH1 expression [80] and cAMP upregulation is also a central component of the axotomy response in dorsal root ganglion (DRG) neurons [81, 82].…”
Section: Bh4 Production and Salvagementioning
confidence: 99%